Pelaksanaan Program Tahfidz Al-Qur’an di Madrasah Ibtidaiyah Al-Awwal Palembang - Hidayat, Hidayat; Gunadi, Gunadi (Pascasarjana IAIN Kudus, 2022)
The formulation of the problem in this research is how to implement the tahfidz Al-Qur'an program at MI Al-Awwal Palembang. In this study, the type of research used was field research with a qualitative nature. Data collection techniques through observation, interviews and documentation. The data analysis technique in this research is using data reduction, data presentation, and data verification. The results obtained that the implementation of the Tahfidz Al-Qur'an Program at MI Al-Awwal Palembang has been going quite well, namely: 1). Judging from the guidance of the tahfidz Al-Qur'an teacher guiding his students in memorizing the Qur'an in accordance with the guidelines or Standard Operating Procedure (SOP) in the madrasa and The implementation of the Tahfidz Program in its implementation has been based on implementation elements consisting of assignments, coordination, motivation and direction, so that the activities at MI Al-awwal have run well. The supporting factors for the implementation of the tahfidz Al-Qur'an program at MI Al-Awwal Palembang, namely: Good physical and psychological infrastructure. Awards or rewards (exemption of school fees, installation of vests, certificates), and Young age. While the inhibiting factors for the implementation of the tahfidz Al-Qur'an program at MI Al Awwal Palembang include: Students are not fluent in reading the Qur'an,). Feeling lazy, Not all parents of students pay attention to memorizing students when they are at home.